The accuracy analysis of fully ⁃ guided mucosa ⁃ supported template based computer ⁃ assisted implant surgery - LIU Zhonghao (口腔疾病防治, 2017)
Objective The purpose of this study is to determine the accuracy of implant placement in the edentu⁃ lous jaw using computer planning and fully ⁃guided mucosa ⁃ supported surgical template by Simplant software. Meth⁃ ods 63 implants were placed in 9 patients (11 fully edentulous jaws), 26 implants were placed in upper edentulous jaw and 37 implants in lower edentulous jaw. Preoperatively, first, a cone beam CT was required for patients with radio⁃ graphic template and radiographic template respectively. Therefore, the data of CBCT was inputted in Simplant software by DICOM format, followed by virtual implant planning. Hereafter, a mucosa⁃supported surgical template was designed by dentist and made by Masterilise company to allow implant placement using the template as a guide. To investigate the accuracy of implant placement, a postoperative CBCT scan was obtained and matched to the preoperative scan. The accuracy of implant placement was validated three⁃dimensionally including divations of implant shoulder, apical point, axial angulation and depth. Results The survival rate of 63 implamts for a 6 month to 10 year observation period was 100%. The mean divation of implant shoulder was 0.73 ± 0.53 mm, implant apical point was 1.15 ± 0.62 mm, implant depth was 0.95 ± 0.64 mm and implant axial angulationwas 4.10 ° ± 3.23°. Conclusion Divation between virtual and actual implant was existed and it should be considered preoperatively when virtual implant was planned to avoid injur⁃ ing anatomic structure and keeping surgery safely. Correct manipulation during implant operation are helpful to de⁃ crease the divation of implant placement.